A Qualitative Study of the Separation of Powers in the Criminal Justice System of Kuwait - Alhajri, Abdulrahman F S H (European Journal of Multidisciplinary Studies, 2018)
The present article considers the separation of powers (SOP) in the criminal justice system of Kuwait. The topic is underrepresented in literature, which may be partially attributed to the fact that SOP in criminal justice is not very extensively studied; instead, administrative SOP is usually reviewed. Furthermore, the investigation of the literature devoted to Kuwaiti criminal justice system also reveals the lack of sufficient coverage. Still, some evidence indicates that in Kuwait, executive bodies have notable power over the criminal justice system of the country. This issue, along with the gaps identified in the literature, prompts the present investigation. The article employs a qualitative methodology to gain insights into the topic. In particular, the literature review is used to identify the areas of interest, as well as gaps in the literature, and interviews are employed to fill the gaps and provide additional details and information. The interviews engaged specialists, including the representatives of the three branch of power, as well as lawyers and academics, and prompted them to consider the topic of SOP in Kuwait, especially in the criminal justice system, as well as its strengths, weaknesses, and plans for improvement. The results indicate that the issue of the excessive power of the executive bodies over the criminal justice of the country is not only present; it also causes significant problems and, according to the participants, needs to be eliminated to ensure the protection of human rights. Additional topics like the potential safeguards and alternatives to SOP that can ensure the protection of human rights were also considered. As one of the very few studies that review Kuwaiti criminal justice and SOP, the present article contributes important data on both topics.
Keywords: criminal justice system, separation of powers, law.